Environmental impacts of crop production systems in subtropical plateau regions: case study of Yunnan, China - Yousheng He; Minghao Li; Wei Zhang; Xinping Chen; Zhengxiong Zhao; Zhi Yao (Scientific Reports)
Abstract Excessive fertilisation, improper nutrient management, and specific climatic factors are the main reasons for the high environmental risks associated with agricultural production in subtropical plateau regions. However, quantitative data of environmental impacts and emission reduction potential remain unclear. The development potential of such systems is likely to be significant. In that context, we conducted a case study in Yunnan Province, China, to quantify the environmental impact of crop production from 2002 to 2021. A life cycle assessment method was employed to identify the factors driving environmental impacts, and potential mitigation strategies were proposed. The yield and total nutrient input of grain crops in Yunnan Province increased over the 20-year period, and the environmental footprint of crop production in Yunnan Province was higher than that in other regions. The average annual mean greenhouse gas (GHG) emissions, soil acidification potential (AP), and water eutrophication potential (EP) of crop production from 2002 to 2021 were 837 kg CO2-eq·Mg−1, 15.7 kg SO2-eq·Mg−1, and 2.71 kg PO4-eq Mg−1, respectively. Environmental emissions from crops mainly originate from the application of agricultural inputs (including fertilisers (N, P, and K), pesticides, seed, diesel fuels, and plastic film) during the crop life cycle. There was a significant correlation between surplus nitrogen and environmental impacts. Scenario testing showed that optimised nutrient management practices could increase crop yield and reduce environmental costs. GHG emissions, AP, and EP from the production of rice, wheat, and maize are expected to decrease by 43.0–59.5%, 51.5–64.5%, and 57.4–71.5%, respectively (scenario 4, S4). Based on these findings, we propose that com-prehensive agricultural management measures can reduce the negative impacts of crop production on the environment in subtropical plateau areas and help achieve sustainable agricultural development.